Structure and Functions of Sidekicks - Yamagata, Masahito (Frontiers in Molecular Neuroscience, 2020)
Many of the immunoglobulin superfamily (IgSF) molecules play pivotal roles in cell communication. The Sidekick (Sdk) gene, first described in Drosophila, encodes the single-pass transmembrane protein, Sdk, which is one of the largest among IgSF membrane proteins. Sdk first appeared in multicellular animals during the Precambrian age, and later evolved to Sdk1 and Sdk2 in vertebrates by gene duplication. In flies, a single Sdk is involved in positioning photoreceptor neurons and their axons in the visual system, and is responsible for dynamically rearranging cell shapes by strictly populating tricellular adherens junctions in epithelia. In vertebrates, Sdk1 and Sdk2 are expressed by unique sets of cell types, and distinctively participate in the formation and/or maintenance of neural circuits in the retina, indicating that they are determinants of synaptic specificity. These functions are mediated by specific homophilic binding of their ectodomains and by intracellular association with PDZ scaffold proteins. Recent human genetical studies as well as animal experiments implicate that Sdk genes may influence various neurodevelopmental and psychiatric disorders, such as autism spectrum disorders, attention-deficit hyperactivity disorder, addiction, and depression. The gigantic Sdk1 gene is susceptible to erratic gene rearrangements or mutations in both somatic and germ-line cells, potentially contributing to neurological disorders and some types of cancers. This review summarizes what is known about the structure and roles of Sdks.